2009
DOI: 10.1007/s10439-009-9803-1
|View full text |Cite
|
Sign up to set email alerts
|

A Bioreactor with Compliance Monitoring for Heart Valve Grafts

Abstract: The drawbacks of state-of-the-art heart valve prostheses lead researchers to explore the prospect of using tissue-engineered constructs as possible valve substitutes. It is widely accepted that the mechanical properties of the construct are improved with mechanical stimulation during in vitro growth. We designed a new dynamic bioreactor with the perspective of using decellularized valve homografts as scaffolds in order to produce tissue-engineered valve substitutes. The design guidelines were (a) compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, these bioreactors have major drawbacks. All these systems have a bulky design [20] and work with a lot of tubes [13,21] and screws [3]. In contrast, the bioreactor presented in this study has a compact and clearly arranged design and avoids the use of screws in the sterilized parts for an easy assembly of the bioreactor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these bioreactors have major drawbacks. All these systems have a bulky design [20] and work with a lot of tubes [13,21] and screws [3]. In contrast, the bioreactor presented in this study has a compact and clearly arranged design and avoids the use of screws in the sterilized parts for an easy assembly of the bioreactor.…”
Section: Resultsmentioning
confidence: 99%
“…Another important difference between this bioreactor and the reactors found in literature [20] is that this bioreactor is not only designed for the actual conditioning process. This bioreactor was designed to be an intermediate step between the seeding and evaluation procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The resistances and the inertances were determined according to classical hydraulic laws (Pennati et al, 2004;Idelchik, 2008), which are reported in the additional material. The values of both the aortic root compliance (C ao ) and the systemic impedance simulator components (R cs , R cp , C cp , L cs ) were taken from the literature (Lanzarone et al, 2009;Vismara et al, 2009).…”
Section: Design Methodologymentioning
confidence: 99%
“…In 2009, Vismara and colleagues [102] developed a prototype especially aimed at the production of viable grafts from decellularized human cadaveric valves. The instrument provided a diastolic pulse stimulation (DPS), obtained by applying transvalvular pressurization, while keeping the homograft in its closed configuration [103].…”
Section: Development Of Customized Bioreactorsmentioning
confidence: 99%